2018
DOI: 10.3758/s13428-018-1028-5
|View full text |Cite
|
Sign up to set email alerts
|

Picture perfect: A stimulus set of 225 pairs of matched clipart and photographic images normed by Mechanical Turk and laboratory participants

Abstract: The present study provides normative measures for a new stimulus set of images consisting of 225 everyday objects, each depicted both as a photograph and a matched clipart image generated directly from the photograph (450 images total). The clipart images preserve the same scale, shape, orientation, and general color features as the corresponding photographs. Various norms (modal name and verb agreement measures, picture–name agreement, familiarity, visual complexity, and image agreement) were collected separa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
36
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(39 citation statements)
references
References 62 publications
2
36
0
1
Order By: Relevance
“…For instance, Uttl et al (2006) suggested that a schematic representation of an object, such as a line drawing, might usually be perceived as a representation of a class of object or type, rather than as a representation of an individual object or token, like in the perception of photographs. Previous studies have provided support for the assumption of different sensory and perceptual processes for the identification of photographs and line drawings, such as strong embodiment and associations with real-world tangible objects (Salmon et al, 2014;Saryazdi et al, 2018). Further, similar findings in the previous literature have highlighted visual iconicity as one of the variables that particularly affects the performance of both children and adults.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…For instance, Uttl et al (2006) suggested that a schematic representation of an object, such as a line drawing, might usually be perceived as a representation of a class of object or type, rather than as a representation of an individual object or token, like in the perception of photographs. Previous studies have provided support for the assumption of different sensory and perceptual processes for the identification of photographs and line drawings, such as strong embodiment and associations with real-world tangible objects (Salmon et al, 2014;Saryazdi et al, 2018). Further, similar findings in the previous literature have highlighted visual iconicity as one of the variables that particularly affects the performance of both children and adults.…”
Section: Discussionsupporting
confidence: 65%
“…Manuscript to be reviewed scale, and orientation features between drawings and photographs (Price & Humphreys, 1989;Brodie, Wallace, & Sharrat, 1991;Saryazdi et al, 2018). Of those, the image types and the naming variables examined differed between the different studies.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research with young children showed the impact of visual iconicity on tasks involving the matching of pictures with real objects, with better performance for photographs than for line drawings (Callaghan, 2000;Ganea et al, 2008). More recently, a subtle iconicity effect in picture naming has also been found in adults (Saryazdi et al, 2018). Our results in children using a picture-naming task showed that the more iconic representation (photograph) produced, the better name agreement measures were obtained, better than the measures of less iconic representation (line drawing).…”
Section: Discussionmentioning
confidence: 97%
“…A pioneering normative study is the one reported by Snodgrass and Vanderwart (1980). This consisted of 260 black-and-white line drawings with norms for name agreement, image agreement (or the degree of agreement between the mental Brodeur, Dionne-Dostie, Montreuil, & Lepage, 2010;and Brodeur, Guérard, & Bouras, 2014;in English and French;Saryazdi, Bannon, Rodrigues, Klammer, & Chambers, 2018;in Turkish;Shao & Stiegert, 2016;in Dutch;Moreno-Martínez & Montoro, 2012;in Spanish;Navarrete, Arcara, Mondini, & Penolazzi, 2019;in Italian). Thus, the need for more ecological stimuli than those provided by line drawings has begun to be highlighted.…”
Section: Introductionmentioning
confidence: 99%
“…Other photographic datasets with norms for adults are the set published by Viggiano et al [ 43 ], in English and Italian; the Hatfield Image Test [ 46 ], in English; the C.A.R.E. set [ 47 ] in English; the set of Shao & Stiegert [ 48 ] in Dutch; the set of Saryazdi, Bannon, Rodrigues, Klammer, & Chambers [ 49 ], in Turkish. The ecological version of the Snodgrass and Vanderwart [ 3 ] set [ 42 ] is the only one in Spanish, and has recently been published also in Italian [ 50 ].…”
Section: Introductionmentioning
confidence: 99%